The effect of the preference pyramid strategy on the achievement of first-year intermediate students in the Arabic language subject and developing their positive thinking - ALOBAIDY, Majid (Journal of Tikrit University for Humanities, 2023)
The current research aims to find out the effect of the preference pyramid strategy on the achievement of first-year intermediate students in the Arabic language subject and developing their positive thinking. The researcher used an experimental design with two equal groups, one experimental and the other control. The size of the research sample reached (58) first-year students. The average, the researcher’s reward is equal between the two research groups in the following variables: age The time frame, the Arabic language score for the sixth grade of primary school, the educational level of the parents, and to achieve the research goal, the researcher prepared the first two tools, an achievement test, and the second a positive thinking test. The researcher extracted the validity and reliability of the two tools, and after processing the data statistically using the T-test for two independent samples, the results showed. There was a statistically significant difference at the level of (0.05) between the experimental and control groups in the achievement and positive thinking tests in favor of the experimental group.